2008
DOI: 10.1177/0145482x0810200102
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting the Meaning of the Terms Certified and Highly Qualified for Teachers of Students with Visual Impairments

Abstract: This article investigates the value of the term highly qualified as it relates to teachers of students with visual impairments. Routes to certification of teachers of students with visual impairments in the United States are not uniform and may not always reflect high-quality teacher preparation. A rationale for more stringent national standards of certification is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In concert with describing the gaps in personnel preparation in assistive technology, one must also recognize the current constraints in higher education. Policy makers routinely criticize teacher preparation programs for not adequately preparing students and, at the same time, because of the demand for teachers, specifically in special education, states are increasingly allowing alternate routes to certification that result in less instructional time for preservice teachers (Pogrund & Wibbenmeyer, 2008). Specifically in the field of visual impairments, states like Texas allow teachers to test out of course work and require only two courses at the university level before allowing students to take a state certification examination (Pogrund & Wibbenmeyer, 2008).…”
Section: Percentage Of Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…In concert with describing the gaps in personnel preparation in assistive technology, one must also recognize the current constraints in higher education. Policy makers routinely criticize teacher preparation programs for not adequately preparing students and, at the same time, because of the demand for teachers, specifically in special education, states are increasingly allowing alternate routes to certification that result in less instructional time for preservice teachers (Pogrund & Wibbenmeyer, 2008). Specifically in the field of visual impairments, states like Texas allow teachers to test out of course work and require only two courses at the university level before allowing students to take a state certification examination (Pogrund & Wibbenmeyer, 2008).…”
Section: Percentage Of Responsesmentioning
confidence: 99%
“…Policy makers routinely criticize teacher preparation programs for not adequately preparing students and, at the same time, because of the demand for teachers, specifically in special education, states are increasingly allowing alternate routes to certification that result in less instructional time for preservice teachers (Pogrund & Wibbenmeyer, 2008). Specifically in the field of visual impairments, states like Texas allow teachers to test out of course work and require only two courses at the university level before allowing students to take a state certification examination (Pogrund & Wibbenmeyer, 2008). Although many preservice teachers choose to continue with course work after they become certified by testing, there are some who become completely dependent on on-the-job training to meet the needs of their students.…”
Section: Percentage Of Responsesmentioning
confidence: 99%
“…Six states currently require passing of an examination with no associated experience or course work. Other states require as many as 11 courses and completion of supervised practicum before individuals are eligible to take a qualification exam (Pogrund & Wibbenmeyer, 2008). The differences in certification requirements suggest a lack of agreement regarding the skills and experience necessary for instructors of the visually impaired, who generally are responsible for braille instruction (Bell, 2010; Frieman, 2006; Johnson, 1996; National Blindness Professional Certification Board, 2009; Rosenblum, Lewis, & D'Andrea, 2010).…”
mentioning
confidence: 99%
“…Braille knowledge and braille instruction are identified by the Council for Exceptional Children (CEC, 2003) as one of the most important skills required for teachers of students with vision impairment (Pogrund & Wibbenmeyer, 2008). Keil's findings (2004) showed that teachers for students with vision impairment believed that braille should exist as a course in their training.…”
Section: Discussionmentioning
confidence: 99%